Visualization of graph databases on mobile clients - Shine, Htet Aung (2019)
With the rise in popularity of social media and interconnected of data between multiple faceted software, visualizing datasets and extracting useful patterns from them have become increasingly important to stay ahead of the competitions in business world. Contrary to relational databases, graph databases in computing are databases which use graphs as the core data structure to represent nodes, edges and properties. Depending on the database, the underlying storage vary. Some databases use normal relation engine to store the data in a table, or key value storage. The application interface to query the graph database also varies, and there are different languages to accomplish the task, e.g Gremlin, SPARQL, Cypher, etc. In this project, we present an iOS application to interact and visualize the graph database using Neo4j. This application was tested on a movie graph with 63,042 nodes (over 12,000 movies and 50,000 actors) and 106,651 relationships, achieving sub-second response time between the server and the client.